Interaction of E-Service Quality, Experiential Marketing, Trust, and Satisfaction on Repurchase Intention - Rahmania, Maulida Afiya; Wahyono, Wahyono (Management Analysis Journal, 2022)
The purpose of this study was to test the influence of e-service quality, experiential marketing, trust, and satisfaction on repurchase intentions. The population in this study was Bukalapak consumers with a sample number of 98 respondents. Sampling methods use convenience sampling techniques. Sample analysis method using Partial Least Square (PLS) with SmartPLS 3.0 program. The results showed that e-service quality had a significant and positive effect on trust and satisfaction. Experiential marketing has a significant and positive effect on trust, but experiential marketing has no significant effect on satisfaction. Trust and satisfaction have a significant and positive influence on repurchase intentions.